Semanticized autobiographical memory and the default – executive coupling hypothesis of aging. (February 2018) - Spreng, R. Nathan; Lockrow, Amber W.; DuPre, Elizabeth; Setton, Roni; Spreng, Karen A.P.; Turner, Gary R.
Abstract: As we age, the architecture of cognition undergoes a fundamental transition. Fluid intellectual abilities decline while crystalized abilities remain stable or increase. This shift has a profound impact across myriad cognitive and functional domains, yet the neural mechanisms remain under-specified. We have proposed that greater connectivity between the default network and executive control regions in lateral prefrontal cortex may underlie this shift, as older adults increasingly rely upon accumulated knowledge to support goal-directed behavior. Here we provide direct evidence for this mechanism within the domain of autobiographical memory. In a large sample of healthy adult participants (n = 103 Young; n = 80 Old) the strength of default – executive coupling reliably predicted more semanticized, or knowledge-based, recollection of autobiographical memories in the older adult cohort. The findings are consistent with the default – executive coupling hypothesis of aging and identify this shift in network dynamics as a candidate neural mechanism associated with crystalized cognition in later life that may signal adaptive capacity in the context of declining fluid cognitive abilities. Graphical abstract: Highlights: Autobiographical memory (AM) is more semanticized in old versus young adults. Lateral PFC and the default network are increasingly coupled with age. We demonstrate greater default-LPFC coupling in resting-state fMRI of older adults. Strength of default-LPFC coupling predicted semanticized AM in old, not young, adults.